Incidencia del Crédito en el Consumo y la Inversión Privada en el Perú: período 2000 - 2010. - Pacheco Cáceda, Diego Augusto (2011)
Our financial system comes recovering in great way up to the registered on 2010, after suffering a fall in the period on 2009, due to the crisis it suppresses originated on the mortgage market of USA. The direct credits grew during the last 11 years, to an average annual rate of 11%. The destination of these credits it has been principally the manufacturing sector, trade, real-estate activities, transport, electricity and mining industry. In addition these credits have very acceptable rates of delinquency, after having on 2000, 9.8% and in the year 2010 register 2.3%. For its part, the demand hospitalizes during the period of analysis it has registered an average annual rate of 5.8%, where the private consumption reached a rate per year of 4.8 %, whereas the private investment obtained 8.9% per year. In case of the PBI the average annual rate reached 5.5% per year. Realizing the model econométrico, it appears that for every S/.1 placed by the financial system, a S/. 0.60 it is destined to the private Consumption, whereas for the case of the private Investment this parameter reaches S/. 0.40. The central aim is to analyze the Incident of the Credit in the Consumption and the Investment Deprived in Peru: period 2000 - 2010. In addition it decided as specific aims to describe the evolution of the credit variables, placements for type of credit, for sector, destination and delinquency; to analyze the development of the economy of the country across the consumption and the private investment and to measure the incident of the credit in the Consumption and the Investment Deprived in the same period 2000 - 2010. It was in use, the methods: analytical - synthetic, deductive - inductive and statistical, which served to separate into its elements the variables and with it to understand the evolution of the Credits of the financial indirect system and the behavior of the Consumption and the Private Investment, year after year. The deductive method, it served us to be able to interpret how the economic dynamism has allowed that the financial companies should enter with great push to several sectors, across his placements and register positive numbers in his investments. The inductive method, it generalized the set of annual behaviors of the variables involved in the investigation. And finally, the statistical method allowed to interpret the behavior of the diverse variables